352 LONG-TERM OUTCOMES FOR PHARMACOLOGICAL AND BEHAVIORAL TREATMENTS FOR METHAMPHETAMINE ABUSE. (1st January 2006) - Lohiya, S.; Dang, J.; Yang, X.; Shoptaw, S.; Ling, W.
Abstract : Background: To date, there are no approved pharmacotherapies for treating methamphetamine abuse; evidence-based treatments for methamphetamine abuse include cognitive behavioral therapy and contingency management. Objective: The purpose was to evaluate long-term outcomes for methamphetamine-abusing individuals assigned to different treatment protocols. Methods: Participants were randomly assigned to one of four 12-week treatment conditions (sertraline only, placebo only, sertaline with contingency management, and placebo with contingency management). All subjects in this study ( N = 180) received a drug counseling platform that involved thrice weekly (Monday, Wednesday, and Friday) 90-minute group sessions of manual-driven cognitive behavioral therapy and provided self-report and urine samples. Results: Subjects reported a clinically relevant reduction in number of days of methamphetamine use from baseline (M = 12.23, SD = 9.00) to termination (M = 4.66, SD = 8.49), at 6-month (M = 4.44, SD = 8.19) and 12-month (M = 5.89, SD = 9.33) follow-up. The percent of subjects providing methamphetamine-free urine at baseline was 49%, which compared to 71%, 68%, and 71% at termination, 6- and 12-month follow-up evaluations. Depression scores also showed significant reductions from baseline (M = 13.96, SD = 8.66) to termination (M = 5.08, SD = 6.56), 6- month (M = 5.26, SD = 5.48) and 12-month (M = 6.17, SD = 7.20) evaluations. Longitudinal analysis of post intervention outcomes indicated no group or time differences. Conclusions: Previous analyses demonstrated that, during treatment, participants in the sertraline condition had significantly poorer abstinence and retention outcomes compared to those in the placebo condition. Furthermore, subjects that received contingency management were significantly less likely to use methamphetamine compared to those not assigned to receive this therapy. The current study adds to previous findings by demonstrating that there were no measurable differences between conditions at the long-term evaluation. Hence, there is no evidence to support further evaluation of sertraline as a putative pharmacotherapy for methamphetamine abuse. The authors gratefully acknowledge support from the following NIH grants: 1P50 DA 18185; MIDARP 1R24 DA017298.